Decolonizing Technology and Society : A Perspective from the Global South - Anna, Bon; Francis, Dittoh; Gossa, Lo; Mónica, Pini; Robert, Bwana; Cheah, Wai Shiang; Narayanan, Kulathuramaiyer; André, Baart (Springer, 2022)
Despite the large impact of digital technology on the lives and future of all people on the planet, many people, especially from the Global South, are not included in the debates about the future of the digital society. This inequality is a systemic problem which has roots in the real world. We refer to this problem as “digital coloniality.” We argue that to achieve a more equitable and inclusive global digital society, active involvement of stakeholders from poor regions of the world as co-researchers, co-creators, and co-designers of technology is required. We briefly discuss a few collaborative, community-oriented technology development projects as examples of transdisciplinary knowledge production and action research for a more inclusive digital society.